Analisis Komunikasi dalam Pembelajaran Kelas III Berbasis NHT Melalui Transcript Based Lesson Analysis (TBLA) - Wann Nurdiana Sari (Universitas Batanghari Jambi, 2022)
Communication is one of the main parts in learning. This communication occurs between teachers and students which makes learning more active. TBLA is a transcript-based lesson analysis that can help uncover an existing problem. The purpose of this study is to analyze communication in class III learning through transcript-based lesson analysis (TBLA). The approach used in this paper is qualitative. The subject of this research is class III SDN Sarimulyo 03. The instruments of this research are documentation and learning analysis sheets with TBLA. The results of this study are the existence of learning communication carried out by the teacher with third grade students making learning activities take place interesting. Good communication makes the quality of students' thinking skills increase. Students are more daring to express their opinion. This condition makes learning activities that take place not only the teacher who dominates. This is due to the participation of students when learning takes place.